Population dynamics of exotic rugose spiralling whitefly, Aleurodicus rugioperculatus Martin (Hemiptera: Aleyrodidae) on coconut as influenced by weather factors and natural enemies - Elango, K.; Jeyarajan Nelson, S. (Journal of Plantation Crops, 2020)
The rugose spiralling whitefly, Aleurodicus rugioperculatus Martin is a new exotic pest occurring in several crops including coconut since 2016 in India. Due to variation in the agro-climatic conditions of different regions, arthropods show varying trends in their incidence also in nature and extent of damage to the crop. Besides, abiotic factors also play a key role in determining the incidence and dominance of a particular pest and their natural enemies in a crop ecosystem. The population dynamics of new exotic whitefly species, A. rugioperculatus and their associated natural enemies was assessed on five-year-old Chowghat Orange Dwarf coconut trees at Coconut Farm of Tamil Nadu Agricultural University. The study indicated that RSW was found throughout the year on coconut and the observation recorded on weekly interval basis shows that A. rugioperculatus population escalated from the first week of July 2018 (130.8 nymphs/leaf/frond) reaching the maximum during the first week of October (161.0 nymphs/leaf/frond) which subsequently dwindled to a minimum during April. The parasitisation by E. guadeloupae on RSW ranged from 31.60 percent in Aug. 2018 to 57.60 percent in December 2018. The association of biotic and abiotic factors with A. rugioperculatus population showed a negative correlation with E. guadeloupae and C. montrouzieri. There was a significant positive correlation between maximum temperature and minimum temperature as well as relative humidity. However, rainfall showed a negative correlation with A. rugioperculatus population.